Advances in antiplatelet therapy for acute coronary syndromes. Issue 1041 (22nd February 2012) - Contractor, Hussain; Ruparelia, Neil
Abstract : Admissions to emergency care centres with acute coronary syndromes remain one of the principal burdens on healthcare systems in the Western world. Early pharmacological treatment in these patients is crucial, lessening the impact on both morbidity and mortality, with the cornerstone of management being antiplatelet agents. While aspirin and clopidogrel have been the drugs of choice for nearly a decade, an array of newer, more potent antiplatelet agents are now available or in late stage development. Data are rapidly gathering suggesting these agents have superior anti-ischaemic properties, improving patient outcomes, but that for some agents increased vigilance and appropriate patient selection may be necessary to guard against bleeding complications. In this review, the authors aim to deliver an overview of the changing field of antiplatelet therapy and provide information about the relative risks and benefits of these newer agents, many of which will be entering widespread clinical use imminently.